Investigation of Formation Fluid During the Development of Fields on the Kara Sea Shelf - E. I. Inyakina; E. E. Levitina; K. O. Ryabikova; V. V. Inyakin (Наука. Инновации. Технологии)
Introduction. With the expansion of offshore drilling and the distance of fields from the coastline, the number of production wells located in difficult underwater geological conditions is increasing, which complicates research. For example, the Yurkharovskoye field is located in a strip along the Tazovsky Peninsula under the waters of the Kara Sea. At the same time, the data obtained from the results of research are necessary when calculating reserves and designing the development of hydrocarbon deposits.Materials and research methods. Modeling of the operating conditions of the field under various thermodynamic conditions was carried out in order to determine the effect of water vapor and oil fractions on condensate losses during the development of the deposit [6–9]. The experiments were carried out to determine the amount of condensate in the reservoir gas, the physicochemical properties of hydrocarbons, and the effect of heavy oil fractions on condensate recovery [5, 10]. Prediction of condensate losses in the reservoir depending on the influence of negative factors must be taken into account when calculating hydrocarbon reserves and drawing up a field development project [11, 13].Research results and their discussion. In the studied part of the section of the Yurkharovskoye field, located on the shelf of the Taz Bay, gas deposits were identified in the Aptian-Albian-Cenomanian complex and gas condensate deposits with oil rims in the Neocomian complex. The selection of development objects was based on a set of geological and geophysical data, the main of which are the presence of reservoirs and seals in the section and a single hypsometric position of the GWC or WOC in the case of an oil and gas condensate deposit. Correlation of well sections and identification of productive formations was based on the choice of benchmarks, the similarity of well logs, taking into account the nature of reservoir saturation and well test results. As a result of experimental PVT studies, the influence of water vapor and oil fractions as an integral part of the hydrocarbon system on the reservoir losses in the deposit was determined. The analysis of the performed studies confirmed that multicomponent hydrocarbon systems consist of a mixture of gas, condensate and water vapor, as well as oil fractions, which significantly changes the properties of the system and the dynamics of its phase processes during the development of the Yurkharovskoye field.Conclusions. The conducted PVT-experiments in order to identify the effect of water vapor and oil components that are part of natural gas showed that the predicted current and final condensate recovery factors are overestimated. An analysis of the research results revealed a different effect of water vapor on reservoir losses of hydrocarbons in the deposit due to an increase in partial pressure. In the presence of formation water in the gas condensate system, the CFC value decreased to 4-5%. Thus, the reason for the increase in reservoir losses of condensate in the deposit during the development of oil and gas condensate fields on the shelf of the Kara Sea was determined.